(AB`+AC`)(B`+C`)+AB`D

First, I factored the A out:

A(B`+C`)(B`+C`)+AB`D

x.x=x, so:

A(B`+C`)+AB`D

Now I am stuck. Any suggestion on the next step to take?

Printable View

- August 31st 2010, 06:24 PMMattpdSimplify the expression using Boolean algebra?
(AB`+AC`)(B`+C`)+AB`D

First, I factored the A out:

A(B`+C`)(B`+C`)+AB`D

x.x=x, so:

A(B`+C`)+AB`D

Now I am stuck. Any suggestion on the next step to take? - August 31st 2010, 08:30 PMMatter_Math
Now expand :

A(B`+C`)+AB`D

AB` + AC` + AB`D

[AB` + AB`D] + AC //Use the identity X + XY = X + Y - August 31st 2010, 10:27 PMIsomorphism
I have to nitpick when the word 'simplify' appears. I think it is not well defined....

The word 'simplify' is especially not well defined for Boolean Algebra. The questions should be of the form prove one expression is another. Certain awful looking expressions in minterm expansion look compact in the maxterm expansions.

A(B'+C') + AB'D = AB'(1 + D) + AC' = AB' + AC' = A(B'+C') = A(BC)' = (A' + BC)'

You see, all the three expressions (namely A(B'+C'), A(BC)', (A' + BC)' ) are equal. So how do we decide which is "simple"?